2022
DOI: 10.1136/ejhpharm-2022-003258
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk prediction model for linezolid-induced thrombocytopenia in elderly patients

Abstract: ObjectivesLinezolid is the first oxazolidinone antimicrobial agent developed for treating multi-drug-resistant gram-positive bacterial infections. The study aimed to investigate the risk factors of linezolid (LI)-induced thrombocytopenia (LI-TP) and to develop and validate a risk prediction model to identify elderly patients at high risk of developing LI-TP during linezolid therapy.MethodsA retrospective cohort study was performed at Zhongshan Hospital, FuDan University, China. The study involved elderly Chine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The included studies used various approaches to retrieve or generate ADE labels and could broadly be categorized into 3 categories: 5 category I studies using ADEs that were registered by healthcare providers (20%), 30 , 33 , 51–53 3 category II studies using adverse event signals followed by a(n) (formal) ADE causality assessment (12%), 43 , 44 , 46 and 15 category III studies using adverse event signals without a(n) (formal) ADE causality assessment (60%). 31 , 34–39 , 41 , 42 , 45 , 46 , 48–50 , 54 Studies in the first category retrieved International Classification of Diseases version 9 or 10 codes (ICD-9 or ICD-10) 55 , 56 that explicitly describe a causal relation between a drug and an adverse symptom (eg, ICD-10 code I95.1: Hypotension due to drugs ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies used various approaches to retrieve or generate ADE labels and could broadly be categorized into 3 categories: 5 category I studies using ADEs that were registered by healthcare providers (20%), 30 , 33 , 51–53 3 category II studies using adverse event signals followed by a(n) (formal) ADE causality assessment (12%), 43 , 44 , 46 and 15 category III studies using adverse event signals without a(n) (formal) ADE causality assessment (60%). 31 , 34–39 , 41 , 42 , 45 , 46 , 48–50 , 54 Studies in the first category retrieved International Classification of Diseases version 9 or 10 codes (ICD-9 or ICD-10) 55 , 56 that explicitly describe a causal relation between a drug and an adverse symptom (eg, ICD-10 code I95.1: Hypotension due to drugs ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2 of these studies, formal ADE causality assessments using the Naranjo probability scale were applied. 43 , 44 Studies in the last category only retrieved adverse event signals without a subsequent (formal) ADE causality assessment. Various abnormal clinical findings were used as adverse event signals, among which: ICD-9 or ICD-10 codes that only described certain symptoms, abnormal lab values, abnormal electrocardiogram (ECG) findings, medication administrations combined with abnormal ECG findings, and medication administrations combined with mental status change assessments or skin and pain assessments.…”
Section: Resultsmentioning
confidence: 99%
“…We read with interest the recently published article by Qin et al 1 The authors stated that a range of factors were risk factors of linezolid-induced thrombocytopenia (LI-TP) in elderly patients. These risk factors were estimated glomerular filtration rate (eGFR), being admitted to an intensive care unit (ICU), baseline platelet counts and concomitant piperacillin-tazobactam.…”
mentioning
confidence: 99%
“…Renal function injury is associated with an increased risk of LI-TP 6. Qin et al showed that the LI-TP risk prediction model exhibited a good discriminative power in the training set and validation set,1 the model is useful for treatment planning of patients with chronic kidney disease because eGFR as an independent risk factor could influence LI-TP. As a screening tool, the LI-TP risk prediction model can display pertinent information to guide clinicians and clinical pharmacists thus avoiding thrombocytopenia, which can be a serious side effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation